In vitro antioxidant and free radical scavenging activity of different parts of Tabebuia pallida growing in Bangladesh. (December 2015) - Rahman, Md.; Islam, Md.; Biswas, Mohitosh; Khurshid Alam, A.
Abstract Background In humans, many diseases are associated with the accumulation of free radicals. Antioxidants can scavenge free radicals and minimize their impact. Therefore, the search for naturally occurring antioxidants of plant origin is imperative. Here, we aimed to investigate the antioxidant and free radical scavenging properties of methanolic extracts fromTabebuia pallida (T. pallida ) stem bark (TPSB), root bark (TPRB), leaves (TPL), and flowers (TPF). Methods The antioxidant and free radical scavenging activity were determined by several standard methods using spectrophotomer. Total phenolic and flavonoid contents were estimated using Folin-Ciocalteu reagent and aluminum chloride colorimetric assay methods, respectively. Results Among the extracts, TPL showed the highest total antioxidant capacity followed by TPRB, TPF, and TPSB. Based on DPPH and hydroxyl radical scavenging activity, TPL showed strong scavenging activity (91.05 ± 1.10 and 62.00 ± 0.57) with IC50 of 9.20 ± 0.28 and 46.00 ± 2.84 μg/mL, respectively when compared with standard BHT (IC50 of 7.00 ± 0.25 μg/mL) and CA (75.00 ± 0.14 μg/mL). These results suggest that TPL had the highest radical scavenging activity among the extractives that closely resembled the standard's. In lipid peroxidation inhibition assay, TPL exhibited the most potent inhibitory activity (83.18 ± 2.12 %) with IC50 of 12.00 ± 2.12 μg/mL, which closely resembled standard CA (IC50 of 10.50 ± 0.28 μg/mL). Also, the reducing capacity on ferrous ion was in the following order: TPL > TPRB > TF > TPSB. The phenolic and flavonoid contents of TPL were higher than other extractives. A positive correlation (p value <0 .001) was observed between phenolic content and free radical (DPPH· and· OH) scavenging efficiencies and lipid peroxidation inhibition activity. Conclusion Methanolic extract ofT. pallida leaf is a potential source of natural antioxidants and serves as an effective free radical scavenger and/or inhibitor. Hence, T. pallida might be a good plant-based pharmaceutical product for several diseases caused by free radicals.